2018
DOI: 10.1037/apl0000286
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial response to client-instigated victimization: The roles of forgiveness and workgroup conflict.

Abstract: We investigate forgiveness as a human service employee coping response to client-instigated victimizations and further explore the role of workgroup conflict in (a) facilitating this response, and (b) influencing the relationship between victimization and workplace outcomes. Using the theoretical lens of Conservation of Resources (Hobfoll, 1989), we propose that employees forgive clients—especially in the context of low workgroup conflict. From low to moderate levels of client-instigated victimization, we sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 136 publications
(245 reference statements)
0
19
0
Order By: Relevance
“…63 Forgiveness, in part, can be viewed as a prosocial change in individuals' thoughts, emotions, or behaviors toward themselves, others, or situations. 64 Such change can include improved awareness, thoughts, and acceptance of strong negative emotions such as anger; development of empathy toward oneself, others, or situations; modification of thoughts and release of previously unsatisfied needs; and starting a new life, all of which lead to improved QOL. 65 Among the demographic and clinical characteristics, age and education were significant predictors of health-related QOL.…”
Section: Discussionmentioning
confidence: 99%
“…63 Forgiveness, in part, can be viewed as a prosocial change in individuals' thoughts, emotions, or behaviors toward themselves, others, or situations. 64 Such change can include improved awareness, thoughts, and acceptance of strong negative emotions such as anger; development of empathy toward oneself, others, or situations; modification of thoughts and release of previously unsatisfied needs; and starting a new life, all of which lead to improved QOL. 65 Among the demographic and clinical characteristics, age and education were significant predictors of health-related QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indeed reveals that a lack of forgiveness is associated with lower job satisfaction (Law, 2013;Radulovic et al, 2019), lower work engagement (Little et al, 2007), less commitment to the organization (Basford et al, 2014), more burnout (Booth et al, 2018;Hershcovis et al, 2018) and higher levels of job stress (Cox, 2011). However, almost all evidence regarding the association between forgiveness and work outcomes relies on cross-sectional designs.…”
Section: Forgiveness and Work Outcomesmentioning
confidence: 99%
“…First, our research addressed and confirmed an association between negative customer treatment and service sabotage among gig workers, which deepens the negative impact of customer mistreatment. Previous negative customer treatment literature focused on regular employees, and to our knowledge, no studies explored how gig worker response to customer mistreatment ( Booth et al, 2018 ; Amarnani et al, 2019 ; Cheng et al, 2020 ; Lavelle et al, 2021 ). In the context of the platform economy, the relationships between organizations and gig workers are characterized by poor employment relationships, which is cooperative-oriented rather than traditional strong control relationships ( Fleming, 2017 ).…”
Section: Discussionmentioning
confidence: 99%